2018
DOI: 10.3390/molecules23092120
|View full text |Cite
|
Sign up to set email alerts
|

The Liver Protection Effects of Maltol, a Flavoring Agent, on Carbon Tetrachloride-Induced Acute Liver Injury in Mice via Inhibiting Apoptosis and Inflammatory Response

Abstract: The purpose of this research was to evaluate whether maltol could protect from hepatic injury induced by carbon tetrachloride (CCl4) in vivo by inhibition of apoptosis and inflammatory responses. In this work, maltol was administered at a level of 100 mg/kg for 15 days prior to exposure to a single injection of CCl4 (0.25%, i.p.). The results clearly indicated that the intrapulmonary injection of CCl4 resulted in a sharp increase in serum aspartate transaminase (AST) and alanine transaminase (ALT) activities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…Previous studies have shown that maltol inhibited hexanal oxidation in a dose-dependent manner, and neuroprotective effects of maltol against oxidative stress were also proposed by Kim and Wei et al [13,14]. Importantly, our previous study confirmed its potent antioxidant properties in TAA (thioacetamide) and alcohol-induced hepatic injury in vivo, which might be attributed to the prevention of lipid peroxidation and alleviation of the inflammation response [15,16,17].…”
Section: Introductionsupporting
confidence: 82%
“…Previous studies have shown that maltol inhibited hexanal oxidation in a dose-dependent manner, and neuroprotective effects of maltol against oxidative stress were also proposed by Kim and Wei et al [13,14]. Importantly, our previous study confirmed its potent antioxidant properties in TAA (thioacetamide) and alcohol-induced hepatic injury in vivo, which might be attributed to the prevention of lipid peroxidation and alleviation of the inflammation response [15,16,17].…”
Section: Introductionsupporting
confidence: 82%
“…After DMM, the maltol treatment group received a dose of maltol for 100 mg·kg −1 ·day −1 (dissolved in saline, administered by oral gavage every day for 8 weeks) 44 . Simultaneously, mice in the DMM alone group received an equal amount of saline.…”
Section: Methodsmentioning
confidence: 99%
“…In these years, it is recognized that maltol prevents renal injuries by suppressing PI3K/AKT signalling pathway 19 . What's more, maltol has the protective property for oxidative stress such as glaucoma and attenuates liver apoptosis inflammation by inhibiting the NF‐κB signalling pathway 20 . Nevertheless, the protective effect of maltol in OA is still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Meyer is a perennial herb that grows slowly [1], and has a long history of medicinal use in traditional Chinese medicine. Ginseng has numerous pharmacological effects on humans, including acting against tumors, as an antioxidant, to inhibit fat accumulation [2,3,4], improving immunity, improving erectile function, and to help combat cardiovascular and cerebrovascular disease [5,6,7,8,9,10,11]. These benefits come with few adverse reactions or side effects.…”
Section: Introductionmentioning
confidence: 99%